Hoesle, V. (2003). El tercer mundo como problema filosófico y otros ensayos. Bogotá: Centro Editorial Javeriano. Número de páginas: 141. - Flórez Flórez, Alfonso; Pontificia Universidad Javeriana (2004)
null